2007
DOI: 10.1002/mus.20805
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian statistical MUNE method

Abstract: We have developed a new method of motor unit number estimation (MUNE) for assessing diseases such as amyotrophic lateral sclerosis (ALS). We used data from the whole stimulus-response curve and then performed a Bayesian statistical analysis. The Bayesian method uses mathematical equations that express the basic elements of motor unit activation after electrical stimulation and allows for the sources of variability and uncertainty in this formulation. The Bayesian MUNE method was used to determine the most prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…The CMAP scan involves gradual increments in stimulus intensity with the subsequent measurement of the CMAP size [72][73][74][75][76]. It is attractive because it studies all of the motor units in a muscle, and has been shown to measure effectively the decline in motor unit number across a range of different rates of disease progression [74].…”
Section: The Cmap Scanmentioning
confidence: 99%
See 1 more Smart Citation
“…The CMAP scan involves gradual increments in stimulus intensity with the subsequent measurement of the CMAP size [72][73][74][75][76]. It is attractive because it studies all of the motor units in a muscle, and has been shown to measure effectively the decline in motor unit number across a range of different rates of disease progression [74].…”
Section: The Cmap Scanmentioning
confidence: 99%
“…It is attractive because it studies all of the motor units in a muscle, and has been shown to measure effectively the decline in motor unit number across a range of different rates of disease progression [74]. However, at present, applications either require off-line analysis (Bayesian MUNE) [73,74], or have not been validated across the different stages of disease progression [77].…”
Section: The Cmap Scanmentioning
confidence: 99%
“…Using rate of decline as well as variability, hypothetical power analyses suggested that this measure might reduce both sample size and study duration in phase II trials. Other new MUNE methods, including MUNIX (90) and Bayseian MUNE (91,92) are also being developed. While no physiological method of motor unit number estimation has been validated against anatomical motor unit counts, their use as potential endpoints in clinical trials shows great promise.…”
Section: Neurophysiology Biomarker Sourcesmentioning
confidence: 99%
“…At least two consecutive MUNE measures are usually performed on each patient to verify the consistency of our results; when required, further estimation was made until the MUNE was clearly stable. The mean of the two or more tests was calculated (Henderson et al, 2007). The results showed an excellent reproducibility with test-retest correlation coefficients ranging from 0.75 to 0.86 (Sartucci et al, 2007).…”
Section: Methodological and Technical Considerationsmentioning
confidence: 99%